Sourcing antimicrobial agents from Globimetula braunii: An in silico molecular docking and dynamic approach - Oriola, Ayodeji O.; Kar, Pallab; Oyedeji, Adebola O. (Journal of Phytology, 2024)
The continued emergence of multi-drug resistance pathogens has been a major setback to lifting the burden of infectious diseases, especially bacterial illnesses. Natural- and/or nature-inspired compounds have so far become a therapeutic backbone on which many novel antibacterial agents are optimized. It is against this backdrop that we used an in silico molecular interaction-based approach to screen five previously identified compounds from Globimetula braunii, for lead inhibitors against bacterial illnesses. The compounds were chromatographed from the leaf ethyl acetate fraction and were characterized by spectroscopic means as 13,27-cycloursane (1), 13,27-cycloursan-3-one (2), methyl-3,5-dihydroxy-4-methoxybenzoate (3), 3-methyl-4-hydroxybenzoate (4), and 2-methoxyphenol (5). Upon their molecular docking at the active pocket of the Staphylococcus aureus gyrase B and the Escherichia coli DNA gyrase, 2 showed the highest binding affinities, with energy scores of -10 and -9.6 Kcal/mol. These were better than the standard antibiotics, Ampicillin (-7.5 and -8.0 Kcal/mol), and Ciprofloxacin (-6.9, -8.4 Kcal/mol). Further evaluation of the most promising compound 2 by molecular dynamics simulation showed the mean RMSD values of the 13,27-cycloursan-3-one - E. coli DNA gyrase protein complexes (complex 1) and 13,27-cycloursan-3-one - S. aureus gyrase B protein (complex 2) to be 0.7 and 0.9 Ǻ respectively, attaining stability at 102 and 108 ns. In contrast, complexes 1 and 2’s RMSF analysis revealed the fewest fluctuations and was generally stable over the course of the 120 ns. In conclusion, 13,27-cycloursan-3-one is unquestionably the most promising inhibitory candidate against the bacterial growth protein DNA gyrase, hence, it can be considered as a druggable substance against bacterial disease.